Intertextual Interweaving’s and Sociocultural Reflections in Tahir Malik's 'Shaytanat': An Analysis and Context of Uzbek Literary Tradition of The Late 20th Century - Yulduz Makhmudova Askarovna (Zien Journals, 2023)
Within the context of Uzbek literature of recent decades, this analysis focuses on the phenomenon of Tahir Malik’s novel “Shaytanat”. By examining the dissonance between critical reception and its popularity among readers, the study aims to deconstruct several key thematic and structural aspects of the work. Particular attention is given to the influence of classical Uzbek literature on the novel’s narrative and the integration of Islamic texts into its structure. Through comparative analysis with other works from the same period, the article also calls for a deeper understanding of the cultural-historical context in which “Shaytanat” was both created and received
Keywords: novelistics; literary criticism; Uzbek literature; cultural-historical context